Screening, Characterization and Identification of Sophorolipid-Producing Yeast Isolated from Palm Oil Effluent Polluted Soil - Williams, K. F.; Agwa, Obioma; Abu, Gideon O. (Sciencedomain International, 2021)
This study investigated the screening, characterization and identification of sophorolipid-producing yeast isolated from palm oil effluent polluted soil. Place and Duration: Two soil samples impacted with palm oil mill effluent were obtained from Elibrada and Rumuche in Emohua Local Government Area, Rivers State, Nigeria, between March 2020 and September 2021. Methodology: The soil samples were analyzed for physicochemical, geotechnical and microbiological qualities. The yeast isolates were identified using biochemical and 16S ITS molecular approaches. The isolates were screened for hydrocarbon degradation and sophorolipid production. The sophorolipid production was evaluated using emulsification index (E24), haemolytic activity, oil spread activity, drop collapse and blue agar plate assay (Cetyl trimethyl ammonium bromide CTAB Method). Results: The pH of the Palm oil mill effluent -impacted soil ranged between pH 6.18 to 6.34 the electrical conductivity value for Elibrada and Rumuche were 20.84 µS/cm and 80.19 µS/cm respectively while that of the unpolluted soil was 220.13 µS/cm. Permeability of the soil from Elibrada was 2.7 cm/s, Rumuche had 1.3 cm/s while the unpolluted soil had 5.6 cm/s. Total organic carbon for soil samples from Rumuche was 4.92%, Elibrada had 6.13% while the unpolluted soil had 8.74%. Oil and grease component for the Rumuche soil was 10500 mg/kg, Elibrada had 7200 mg/kg and the unpolluted soil had 28.0 mg/kg. Total fungal count for Rumuche soil samples was 3.8 × 104 CFU/g while Elibrada had 3.2 × 104 CFU/g. Eighty percent (80%) of the isolates were Candida spp. while 20% were Saccharomyces sp. There were four bands separated which were denoted as ITS 600bp and a Ladder L which was 500bp. The phylogenetic construct showed that the Y8 was 70.2% similar to Candida parapsilosis. The isolate Y3 was 95.8% similar to Candida haemulonis. Isolate Y9 had 100% similarity with Pichia kudriavzevii while Y13 had a 97.4% identity with Saccharomyces cerevisiae the GENBANK accession numbers were Candida haemulonis MW182014, Candida parapsilosis MW182015, Pichia kudriavzevii MW182016 and Saccharomyces cerevisiae MW182017. Conclusion: There is an increasing concern to develop a process for microbial isolation and characterization for effective biotechnological advancement using impacted environmental media as a bioresource.
Journal of Advances in Microbiology 21(12): 1-16, 2021; Article no.JAMB.76592
Keywords: Palm oil; polluted soil; screening; sophorolipid; yeast isolated; O. Akaranta; STEM; University of Port Harcourt